Relationship of Marketing Mix to Outpatient Loyalty at Cut Meutia Medika Nusantara Langsa General Hospital - Elvina Sari (Fakultas Kesehatan Masyarakat, Universitas Pancasakti, Makassar, 2025)
Patient loyalty is one of the key factors that hospitals must strive to achieve. This is because increasing patient loyalty can provide long-term benefits. This study is analytical in nature, using a cross-sectional study design. The independent variables in this study are process mix and physical evidence mix, while the dependent variable is patient loyalty. A total of 97 respondents were selected using the accidental sampling technique. Data were analyzed using univariate and bivariate analysis with the Chi-Square test and presented in frequency distribution tables. The results showed a significant relationship between the process mix (p-value = 0.000) and physical evidence mix (p-value = 0.000) with outpatient loyalty at RSUCM Medika Nusantara. The study concluded that the process mix and physical evidence mix in the outpatient department were still categorized as suboptimal and had an impact on outpatient loyalty at RSUCM Medika Nusantara. It is recommended that the hospital continuously evaluate its service processes and improve the availability of necessary facilities to enhance patient comfort during visits. This will ultimately lead to increased patient satisfaction and loyalty.